EVALUATION OF FRIESIAN HOLSTEIN GRADE COWS FERTILITY BASED THE LEVEL OF MILK UREA - Widayati, Diah Tri; Suranindyah, Yustina Yuni; Rahmah, Laelatul; Widyobroto, Budi Prasetyo (Jurnal Kedokteran Hewan, 2017)
This study was conducted to evaluate fertility grade of Friesian Holstein cows based on milk urea levels. A number of eight cows which fulfill the criteria of not pregnant and in second to sixth lactation, produced milk of 2.5 liters/day, and body weight ranging from 400-450 kg were used in this research. The cows were given fodder that consisted of 30 kg of forage and 10 kg of a mixture of concentrate (pollard, pulp out, and molasses), in the morning and afternoon. Milk and blood samples were taken once a week for five weeks in the morning before fed. Milk urea levels were measured using the urea FS (DiaSys) and blood samples were tested using enzyme linked immuno-sorbent assay (ELISA) with the progesterone hormone kit (DRG, Germany). The variables measured were pregnancy rate, service per conception (S/C), days open, and progesterone levels. Reproduction and milk urea levels data were analyzed by linear regression to determine the relationship between two variables. Progesterone data were analyzed descriptively. The results showed that the average calving interval, days open, and S/C were 607.5170.27 days; 341.25187.65 days; and 2.412.32 days, respectively. The average of milk urea levels was 14.162.55 mg/dL. Regression analysis showed a significant effect (P0.05) and negative correlation between milk urea level and S/C. The average of non-pregnant progesterone hormone level was 12.047.13 ng/mL. In conclusion, the fertility grade of Friesian Holstein cows decreased when the milk urea level at 14.16 mg/dL and non-pregnant progesterone at 12.047.13 ng/mL.